Represje niemieckie na Kresach Wschodnich II Rzeczypospolitej 1941–1944 - Hryciuk, Grzegorz (Pamięć i Sprawiedliwość, 2008)
The territories of eastern Poland annexed in 1939–1940 by the Soviet Union, in the summer of 1941 were under the German occupation and they were incorporated into the new Reichskommissariat Ukraine and Reichskommissariat Ostland, the General Gouvernement or – as in the case of two eastern poviats of Białystok Province and a small part of Polesie Province – incorporated into Białystok District, subordinated to the Reichsverteidigungskommissar for East Prussia. The basic principles of the occupation policy of the Third Reich were formulated before the outbreak of the Soviet-German war. It seems that what affected their implementation, especially resorting to terror, were the attitudes of local communities including their willingness to co-operate, the exhibited level of adaptation and resistance as well as the course of events at the fronts and the evolution of general principles of the occupation policy inspired by those trends. To some extent, the character of the policy also depended on the personal features of the top offi cials of German administration who implemented it. That is why the reprisal measures directed against different ethnic groups in particular territories differed – the regime was relatively mild as far as Lithuanians in the General Reichskommissariat Lithuania or Ukrainians in Galicia district were concerned and more severe in the case of Ukrainians in Volhynia and Belorussians in the General Reichskommissariat Belorussia. The most ruthless terror was directed against Jews. The extermination of Jews started as early as the summer of 1941 when German operational groups (Einsatzgruppen) entered into the Polish eastern territories. The most intense genocide operations were carried out in 1942. The losses of other nations were lower, and the occupier’s reprisals intensifi ed at the turn of 1942 and 1943 and in 1943–1944, when the North-Eastern Borderlands of the Second Republic of Poland, Polesie and Volhynia became the theater of the great anti-partisan operations and pacification actions organized by the German security forces. The demographic losses seem to be much higher among Poles, Ukrainians and Belorussians caused by the forced deportations to slave labour into the interior of the Third Reich. The inhabitants of the eastern Borderlands of the Second Republic of Poland incurred heavy losses during the German occupation in 1941–1944, amounting to 1.6–1.7 million casualties that is nearly 15 per cent of the total number of inhabitants. The heaviest losses were infl icted to Jews: 1 100 000 – 1 150 000 persons; nearly all Jewish Borderland inhabitants were murdered. According to the estimates which are still treated as not fi nal and requiring further research and careful verifi cation about 95 000 persons (including 75 000 Jews) lost their lives in the Vilnius County, 500 000 (including 300 000 – 350 000 Jews) in the territories incorporated into the Belorussian Soviet Republic, about 300 000 (including 224 000 Jews) in Volhynia, and not more than 700 000 – 800 000 persons (including 495 000 Jews) in Eastern Galicia were murdered.